Performances of Three Cotton Varieties Cultivated under Economic Threshold Level Based Insecticide Sprayed and Non-Sprayed Conditions - Azad, H.M.S.; Amin, M.R.; Tithi, D.A.; Hossain, S.M.A. (Our Nature, 2012)
Cotton growers of Bangladesh usually cultivate eleven varieties of cotton and abruptly use chemical insecticides for controlling pests. In this study we evaluated the performances of three extensively cultivated varieties (CB9, CB10 and SR05) under economic threshold level (ETL) based insecticide sprayed and non-sprayed conditions. Results showed that number of bolls per plant and yield of the varieties differ significantly and there was found significant difference between the experimental conditions. Our study showed that the variety SR05 produced significantly higher number of bolls (40.5±6.6 /plant) and yield (2498.3±18.9 kg/ha) compared to CB9 and CB10, whereas CB9 produced higher number of seed (36.9±3.7/boll) and seed index (83.4±0.9 g/100 seed) under ETL based insecticide sprayed condition. The ginning out tern (GOT%) and seed germination percentage of the studied varieties did not differ to a significant level. Overall fitness of the varieties indicated that SR05 possesses comparatively better performances for commercial production of cotton in Bangladesh. DOI: http://dx.doi.org/10.3126/on.v9i1.5728